Immunological efficacy of glypican-3 peptide vaccine in patients with advanced hepatocellular carcinoma - Tsuchiya, Nobuhiro; Yoshikawa, Toshiaki; Fujinami, Norihiro; Saito, Keigo; Mizuno, Shoichi; Sawada, Yu; Endo, Itaru; Nakatsura, Tetsuya (Oncoimmunology, 2017)
We have previously conducted a phase I trial to test the efficacy of a glypican-3 (GPC3) peptide vaccine in patients with advanced hepatocellular carcinoma (HCC); however, its immunological mechanism of action remains unclear. Here, we report a pilot study conducted to evaluate the immunological mechanisms of action of this GPC3 peptide vaccine (UMIN-CTR number 000005093). Eleven patients with advanced HCC were vaccinated with the GPC3 peptide in this trial. The primary end point was GPC3 peptide-specific immune response induced by the GPC3 peptide vaccination. The secondary endpoints were clinical and biologic outcomes. We demonstrated that the present vaccine induced GPC3 peptide-specific cytotoxic T lymphocytes (CTLs), which were found to infiltrate into the tumor. Moreover, we established GPC3 peptide-specific CTL clones from a biopsy specimen: these cells exhibited GPC3 peptide-specific cytokine secretion and cell cytotoxicity. The plasma GPC3 level tended to decrease temporarily at least once during the follow-up period. The GPC3-specific CTL frequency after vaccination was correlated with overall survival. The degree of skin reactions at the injection site correlated with the GPC3 peptide-specific CTLs. Furthermore, we sequenced the T cell receptors (TCRs) of tumor-infiltrating lymphocyte (TIL) clones, and confirmed the existence of this TCR repertoire in both tumor tissue and PBMCs. In response to these data, we are developing TCR-engineered T cell therapy using TCR sequences obtained from GPC3 peptide-specific CTL clones for improved efficacy in patients with advanced HCC.